The scarlet letter and postmodernism - Asim Karim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Postmodernism is a convoluted and nebulous term to define as it involves a plethora of major and minor details that appear in a wide variety of areas of study like art, literature, culture architecture, technology, education. Equally problematical is to locate it historically as well as temporally. One of the principal areas of post modernism that continues to inspire critical debate is its strong scepticism of the grand narratives of modernism. Contrary to the modernist focus on hierarchical grand positions, post modernism as Lyotard envisioned it “preaches an appreciation and respect for diversity, for local differences, for the plurality of ways in which human choose to live”. This study aims to analyse Hawthorne’s The Scarlet Letter as a postmodern text for it demonstrates a strong disinclination to uphold logocentric, monologic, absolute, universalist and structured metanarratives. It will be argued that a strong and hierarchical power structure supports and uphold these metanarratives for specific objectives of perpetuation of the governance and authority over the people. Thus, it links Lyotard’s scepticism of metanarratives with Foucault’s discourse of knowledge and power. It will be argued that resistance and opposition to this phenomenon is pre-eminently demonstrated not only by the most marginalized Hester Prynne, but also by Arthur Dimmesdale who has been one of the beneficiaries of these metanarratives. In countering and opposing the metanarratives, both establish a space for the legitimization of pluralism, diversity and heterogeneity as well as post modern liberation from the totalitarian persecution of the marginalized and the dissident voices.